A Review of the Bond Mechanism and Bond Strength of Fiber Reinforced Polymer Rebars to Concrete - borkan alsabha (Misan Journal of Engineering Sciences)
Fiber Reinforced Polymer (FRP) reinforcement bars have been increasingly utilized in reinforced concrete structures over the last two decades, substituting conventional steel reinforcement, particularly in places facing challenging environmental circumstances. A literature review is presented in this article, with the primary focus being on the bond performance of FRP bars to concrete. The purpose of this study is to cover all of the useful contributions that have been made on the bond performance in earlier research. This work is based on results from the collection of experimental data from a total of 1784 pullout tests in the existing literature. The bonding performance of FRP bars with concrete represents an extremely essential characteristic for assembling the FRP bars into corrosion-free reinforced concrete structures. FRP materials, contrary to steel reinforcements, possess non-homogeneous, anisotropic, and elastically linear features, thus resulting in a distinct force transfer mechanism between concrete and reinforcement. The most significant parameters influencing the bonding of FRP bars to concrete were outlined in this paper. The information gathered through the investigation indicated that FRP bars behave effectively as reinforcement components in reinforced concrete structures.